(untitled) (Research, Society and Development, 2022)
Objective: to verify the suspicion of common mental disorders in family members of users of a psychiatric outpatient clinic during the Covid-19 pandemic and analyze the complaints. Method: a cross-sectional study carried out in 2021 with 31 family members of users of a mental health clinic in the city of Rio de Janeiro, Brazil. Data were collected using an instrument with sociodemographic variables and psychosocial aspects of Covid-19 and the Self Report Questionnaire-20 was used to verify common mental disorders. Results: the frequency of suspicion of common mental disorders in the sample was 51.6%. The complaints with the highest frequency of positive responses were: “feeling nervous, tense or worried” (83.1%), “feeling sad lately” (54.8%), “having frequent headaches” (41.9%). In the perception of family members, complaints were associated, mainly with “care for the family member with a mental disorder during the pandemic” (67.7%), “financial problems” (67.7%) and “changes in family routine due to Covid-19” (54.8%). Conclusion: the high frequency of suspicion of common mental disorders and the identified complaints requires the mental health service to support families in order to minimize suffering in the group.